Nuclear spallation in active galaxies - Gallo, L. C.; Randhawa, J. S.; Waddell, S. G. H.; Hani, M. H.; Garcia, Javier; Reynolds, C. S. (Monthly Notices of the Royal Astronomical Society, 2019)
A number of works point to the presence of narrow emission features at unusual energies in the X-ray spectra of active galactic nuclei or to potentially low iron abundances as possible evidence for the spallation of iron. With the imminence of high-resolution calorimeter spectroscopy, the potential to test spallation models in astrophysical sources will soon be possible. Previously determined nuclear spallation reactions of Fe are recalculated making use of improved total inelastic and partial reaction cross-sections that result in different absolute and relative abundances of the main spallation elements Mn, Cr, V, and Ti. The effects of ionization and dynamics near the black hole are examined in simulated spectra with CCD and calorimeter (i.e. Hitomi) resolution. With high resolution, differences in relative abundances and ionization should be detectable if spallation is originating at large distances from the black hole (e.g. torus or disc wind), where blurring is not significant. If spallation were occurring in the inner accretion disc, it would likely be undetected as blurring effects would cause significant blending of spectral features.
CRIS-Team Scopus Importer:2021-04-20
Keywords: accretion; accretion discs; galaxies: active; galaxies: nuclei; nuclear reactions; nucleosynthesis; abundances; X-rays: galaxies